The Correlation between Students’ Vocabulary Mastery and Reading Comprehension of Students at SMA Negeri 13 Makassar - Marwah Achmad; Sujarwo (CV. Eureka Murakabi Abadi, 2022)
Mastery of vocabulary is very important in reading comprehension and determines how well students understand the text. This is the reason for doing this research. The objectives are 1) to determine students' vocabulary mastery and reading comprehension of tenth graders of SMA Negeri 13 Makassar; 2) to determine the correlation between students' vocabulary mastery and reading comprehension of tenth graders of SMA Negeri 13 Makassar. The research method used is the correlational design method with a quantitative approach. The population in this study amounted to 288 students, 36 students were taken from the total population. The sampling technique is using purposive sampling technique. Vocabulary mastery data were collected using multiple choice tests while reading comprehension data were collected using multiple choice and essay tests. The results of this study were then analyzed using the Pearson Product Moment correlation coefficient with the SPSS 22.0 application. The results of statistical calculations between variables X and Y are positive with an rxy of 0.206. Then rxy is compared with r table product moment at a significant level of 5% with a sample of 36 students, it is found that rxy > rtable is 0.546 > 0.329 in a low level of relationship. Therefore, hypothesis one (H1) is accepted while Hypothesis Null (????0) is rejected. It can be concluded that there is a significant correlation between students' vocabulary mastery and students' reading comprehension at SMA Negeri 13 Makassar. This proves that the more English vocabulary the students have, the better their reading comprehension.